Intraneuronal Amyloid Beta Accumulation Disrupts Hippocampal CRTC1-Dependent Gene Expression and Cognitive Function in a Rat Model of Alzheimer Disease. (12th January 2016) - Wilson, Edward N.; Abela, Andrew R.; Do Carmo, Sonia; Allard, Simon; Marks, Adam R.; Welikovitch, Lindsay A.; Ducatenzeiler, Adriana; Chudasama, Yogita; Cuello, A. Claudio
Abstract: In Alzheimer disease (AD), the accumulation of amyloid beta (Aβ) begins decades before cognitive symptoms and progresses from intraneuronal material to extracellular plaques. To date, however, the precise mechanism by which the early buildup of Aβ peptides leads to cognitive dysfunction remains unknown. Here, we investigate the impact of the early Aβ accumulation on temporal and frontal lobe dysfunction. We compared the performance of McGill-R-Thy1-APP transgenic AD rats with wild-type littermate controls on a visual discrimination task using a touchscreen operant platform. Subsequently, we conducted studies to establish the biochemical and molecular basis for the behavioral alterations. It was found that the presence of intraneuronal Aβ caused a severe associative learning deficit in the AD rats. This coincided with reduced nuclear translocation and genomic occupancy of the CREB co-activator, CRTC1, and decreased production of synaptic plasticity-associated transcripts Arc, c-fos, Egr1, and Bdnf . Thus, blockade of CRTC1-dependent gene expression in the early, preplaque phase of AD-like pathology provides a molecular basis for the cognitive deficits that figure so prominently in early AD.